Implementasi Budaya K3 Untuk Mengurangi Risiko Kecelakaan Kerja Pada IKM CV. Sispra Jaya Logam - Siswo Pranoto; Mahmud Akhyar; Abdul Rahman (CV. Multi Kreasi Media, 2026)
The metal Small and Medium Industry (SMI) sector possesses a high potential for workplace accidents, yet awareness regarding Occupational Safety and Health (OSH) often remains low. This community service activity aims to enhance the knowledge, awareness, and skills of workers at CV. Sispra Jaya Logam in implementing OSH principles. The topic was selected due to the partner's high-risk production activities, such as metal cutting and welding, while the implementation of safe work procedures and the use of Personal Protective Equipment (PPE) at the site were still limited. The implementation method included OSH concept socialization, classroom training through presentations and discussions, field practice involving PPE simulations and hazard identification, as well as evaluations through pre-tests and post-tests. The results showed a significant increase in the participants' technical competence. Based on the evaluation, the workers' understanding of OSH improved from an average below 50% before the training to a range between 87% and 100% afterward. Workers are now able to identify potential hazards and understand proper PPE procedures. In conclusion, this activity proved effective in fostering a culture of safety within the SMI environment. The importance of these results lies in creating a healthier and more productive work environment, highlighting the need for continuous assistance to ensure OSH principles are consistently applied in daily production activities.